Improving students' english through problems-solving activities (2001)
We as teachers sometimes notice low motivation and participation during the development of our classes. Students have an aphatic attitude and this creates a bad environment when they work in class. Motivating and creating a good environment in class through our English activities, was the objective of our project. We took problem solving activities as an excellent way to create a good atmosphere in class and change the routine in order to motivate and increase students’ participation. This project was relevant because we explored a new method of teaching English which included different types of activities and our students became active agents in the learning process.